A re-assessment of the safety of silver in household water treatment: rapid systematic review of mammalian in vivo genotoxicity studies - Lorna Fewtrell; Batsirai Majuru; Paul R. Hunter (Environmental Health, 2017)
Abstract Background Despite poor evidence of their effectiveness, colloidal silver and silver nanoparticles are increasingly being promoted for treating potentially contaminated drinking water in low income countries. Recently, however, concerns have been raised about the possible genotoxicity of particulate silver. Objectives The goal of this paper was to review the published mammalian in vivo genotoxicity studies using silver micro and nanoparticles. Methods SCOPUS and Medline were searched using the following search string: (“DNA damage” OR genotox* OR Cytotox* OR Embryotox*) AND (silver OR AgNP). Included papers were any mammalian in vivo experimental studies investigating genotoxicity of silver particles. Studies were quality assessed using the ToxRTool. Results 16 relevant papers were identified. There were substantial variations in study design including the size of silver particles, animal species, target organs, silver dose, route of administration and the method used to detect genotoxicity. Thus, it was not possible to produce a definitive pooled result. Nevertheless, most studies showed evidence of genotoxicity unless using very low doses. We also identified one human study reporting evidence of “severe DNA damage” in silver jewellery workers occupationally exposed to silver particles. Conclusions With the available evidence it is not possible to be definitive about risks to human health from oral exposure to silver particulates. However, the balance of evidence suggests that there should be concerns especially when considering the evidence from jewellery workers. There is an urgent need to determine whether people exposed to particulate silver as part of drinking water treatment have evidence of DNA damage.